Factors influencing nomophobia among undergraduate students in UiTM Kedah / Nurul Nasuha Muhammad Awis Hazrani, Wan Nur Najihah Wan Ali and Adnan Aminuddin - Muhammad Awis Hazrani, Nurul Nasuha; Wan Ali, Wan Nur Najihah; Aminuddin, Adnan (UiTM Cawangan Johor, 2024)
Smartphones have become a necessity in our lives not only as a medium for communication but also as a trading platform for sellers and buyers. Initially, the users of smartphones were among those who are working but now even students use it as teaching and learning tools. The necessity for using smartphones among students emerged during the pandemic Covid-19 when all the classes were conducted online. Hence, the reliance on smartphones has skyrocketed but over-dependence may produce a negative impact on the users. Statistics showed that about 71.4% of Malaysians will check their smartphones even when it does not ring. It was stated that in Southeast Asia, Malaysia smartphone users used an average of 187 minutes per day which was the highest in hours spent on their devices. Hence, this research seeks to identify the factors influencing Nomophobia among undergraduate students in UiTM Kedah. A cross-sectional survey was conducted using a stratified random sampling technique among 214 undergraduate students and the result showed that they have a high level of nomophobia. This study has identified that all variables which are smartphone usage, smartphone addiction, and internet addiction tested have a strong correlation toward Nomophobia among the respondents.